2014
DOI: 10.1186/1880-5981-66-58
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-rock interaction recorded in black fault rocks in the Kodiak accretionary complex, Alaska

Abstract: Ultrafine-grained black fault rocks (BFRs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…Although this result is different from that obtained in previous studies, it is in agreement, in terms of increasing Li concentration, with Yamaguchi et al (2014). Regarding the enrichment of Li, Yamaguchi et al (2014) estimate that reactions with fluids containing a high content of Li occurred at seismogenic depths. In this study, it is suggested that Li and Cs are concentrated due to the similarity of temperatures experienced by the Kodiak accretionary complex and the Nobeoka Thrust.…”
Section: Comparison With Previous Researchescontrasting
confidence: 53%
See 1 more Smart Citation
“…Although this result is different from that obtained in previous studies, it is in agreement, in terms of increasing Li concentration, with Yamaguchi et al (2014). Regarding the enrichment of Li, Yamaguchi et al (2014) estimate that reactions with fluids containing a high content of Li occurred at seismogenic depths. In this study, it is suggested that Li and Cs are concentrated due to the similarity of temperatures experienced by the Kodiak accretionary complex and the Nobeoka Thrust.…”
Section: Comparison With Previous Researchescontrasting
confidence: 53%
“…Fluid-rock interactions along the Chelungpu fault, Taiwan, were investigated by Ishikawa et al (2008), while the Emi accretionary complex, Boso, the Kure Mélange of the Shimanto belt, and the Pasagshak Point thrust in the Kodiak accretionary prism were studied by Hamada et al (2011), Honda et al (2011), and Yamaguchi et al (2014), respectively. Table 1 compares the element redistribution patterns derived from this work to those obtained from previous researches.…”
Section: Comparison With Previous Researchesmentioning
confidence: 99%
“…Rocks in the slip zone of the Taiwan Chelungpu fault showed distinct depletion of or enrichment in fluid-mobile trace elements consistent with coseismic fluid-rock interactions at >350°C and the occurrence of thermal pressurization during the 1999 Chi-Chi earthquake as the permeability of the fault zone is low [Ishikawa et al, 2008;Tanikawa et al, 2009]. Similar geochemical anomalies have been reported in fault rocks from accretionary prisms and another on-land active fault [Hamada et al, 2011;Honda et al, 2011;Ishikawa et al, 2014;Yamaguchi et al, 2014]. However, Ishikawa et al [2008] based their interpretation of geochemical data on the results of laboratory hydrothermal experiments carried out in an autoclave apparatus and obtained after a long reaction time of at least a few days [You et al, 1996;James et al, 2003].…”
Section: Introductionsupporting
confidence: 69%
“…Rocks in the slip zone of the Taiwan Chelungpu fault showed distinct depletion of or enrichment in fluid‐mobile trace elements consistent with coseismic fluid‐rock interactions at >350°C and the occurrence of thermal pressurization during the 1999 Chi‐Chi earthquake as the permeability of the fault zone is low [ Ishikawa et al , ; Tanikawa et al , ]. Similar geochemical anomalies have been reported in fault rocks from accretionary prisms and another on‐land active fault [ Hamada et al , ; Honda et al , ; Ishikawa et al , ; Yamaguchi et al , ]. However, Ishikawa et al .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, feldspar breakdown in fault core is opposite to some other thrusts in subduction setting. For example, plagioclase was newly formed by >350°C water-rock interaction in the fault core of the Pasagshak Point Thrust in the Kodiak accretionary complex, Alaska (Yamaguchi et al 2014), although both the Nobeoka Thrust and the Pasagshak Point Thrust were active at similar background temperatures of approximately 250°C.…”
Section: Factors Controlling Illite Crystallinity Within Fault Zonementioning
confidence: 99%